Culture supernatants of oral cancer cells induce impaired IFN-α production of pDCs partly through the down-regulation of TLR-9 expression. (September 2018) - Han, Nannan; Zhang, Zun; Jv, Houyu; Hu, Jingzhou; Ruan, Min; Zhang, Chenping
Highlights: The proportion of pDCs was significantly higher in OSCC samples than in normal tissue. Decreased TLR9 mRNA expression was associated with a low IFN-α production in tumor-infiltrating pDCs of OSCC patients. Supernatants of OSCC cells negatively regulate TLR-9 mRNA expression and subsequent IFN-α production of pDCs. Oral cancer-derived supernatants down-regulate the pDC-mediated CD4+-T-cell immune response. Careful manipulation of these impaired pDCs may help develop an important alternative immunotherapy for oscc. Abstract: Objectives: The aim of the present study was to investigate whether tumor-derived supernatants down-regulate the immune function of plasmacytoid dendritic cells (pDCs) in oral cancer and the potential molecular mechanisms of this effect. Materials and Methods: Immunohistochemistry (IHC) and flow cytometry were used to detect tumor-infiltrating and peripheral blood pDCs. MTS and flow cytometry were employed to evaluate the immune response of CD4 + T cells. Real-time PCR and ELISA assays were used to identify TLR-7 and TLR-9 expression, IFN-α production and tumor-secreted soluble cytokines. Results: The proportion of pDCs (0.121%±0.043%) was significantly higher in Oral squamous cell carcinoma (OSCC) samples than in normal tissue (0.023%±0.016%) ( P = 0.021). TLR9 mRNA was significantly lower in tumor-infiltrating pDCs and positively correlated to low IFN-α production (r = 0.956; P <0.01). The supernatant of oral cancer cells negatively regulated TLR9 mRNA expression and the subsequent IFN-α production of pDCs, which inhibited the immune response of CD4 + T cells. The neutralizing antibodies blocking assay showed that the specific inhibitory effect of pDC functionality was associated with the soluble fraction of the oral cancer environment, which is mainly mediated by IL-10 and TGF-β cooperation. Conclusion: Tumor-derived supernatants may impair the function of tumor-infiltrating pDCs, which subsequently decreases the immune response of CD4 + T cells in human oral cancer through TGF-β- and IL-10- dependent mechanisms. Careful manipulation of these impaired pDCs may help develop an important alternative immunotherapy for the treatment of oral cancer.